Bibliometric analysis of gig economy - Altanshagai Batmunkh; Maria Fekete-Farkas; Zoltán Lakner (Administrative Sciences, 2022)
Technological advances such as smartphones, mobile applications, and online platforms have enabled a new form of economy, known as a gig economy, at a large scale, in which there is a free-market system allowing organizations (job providers) to hire independent contractors (job seeker). Unlike traditional employer and employee relationships, the gig economy creates opportunities for independent workers to seek short-term contract jobs and temporary positions. This article presents a systematic review of the literature associated with a bibliometric analysis of the global perspective of the gig economy. The study aims to present the analysis of published articles that explore the gig economy. Initially, 2297 documents were retrieved by gig economy as a keyword from Google Scholar, Scopus, and Web of Science between 2014 and 2022. After applying certain criteria, only 686 publications were selected for bibliometrics analysis. The selected articles were used to measure bibliometric indicators and evaluate the research work on the gig economy. Bibliometrics an R package for bibliometric and co-citation analysis was used to achieve the results. VOSviewer was also used to analyze the co-occurrence of the keywords. The results highlight the publication trends, top contributing authors and their countries, most cited articles, keywords, and most contributing journals to the research field.
Keywords: 350; circular economy; platform economy; sharing economy; gig work; digital economy